COMPARATIVE EFFICACY OF ANTIPROGESTIN AND DOPAMINE AGONIST IN THE TREATMENT OF CANINE PYOMETRA - SINGH, L. KIPJEN; PATRA, M K; MISHRA, G K; LINDA, N; SAXENA, A C; DE, U K; KUMAR, H; NARAYANAN, K (The Indian Journal of Animal Reproduction, 2020)
The study was designed to investigate the comparative efficacy of antiprogestin vis-à-vis dopamine agonist in the treatment of pyometra in bitches (n=16) presented to the Referral Veterinary Polyclinic - Teaching Veterinary Clinical Complex, Indian Veterinary Research Institute, Izatnagar. Pyometra was confirmed by presumptive clinical signs and transabdominal ultrasonography and the positive bitches were randomly subjected to two treatment regime, T1 (Mifepristone @ 2.5mg/kg p.o. on day 0, 1 and 10) and T2 (dopamine agonist, Cabergoline @ 5μg/kg, p.o. for 7 days), n=8/group. Cloprostenol @5μg/kg, s/c on alternate days for 7 days was included in both the groups along with empirical fluid and antibiotics. The treatment responses was determined by general clinical examination, changes of blood urea nitrogen, serum creatinine, prostaglandin F metabolites (PGFM) and progesterone (P4) level at pre-treatment and 10 days post-treatment. Recurrence or recovery was recorded on follow up examination and telephonic feedback after 100 days post treatment. A reduction in BUN and P4 concentration was recorded in both the treatment groups. The non-recurrence rate (%) of pyometra in the mifepristone treated bitches was 85.7 percent compared to 51.43 percent in cabergoline (P=0.09) treatment. From this study it can be concluded that addition of mifepristone improved the recovery rate with a reduction of recurrence rate in the medically treated pyometra cases in bitch.